2022
DOI: 10.31083/j.jin2102072
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodin suppresses pyroptosis and exerts neuroprotective effect in traumatic brain injury model by inhibiting NLRP3 inflammasome signaling pathway

Abstract: Traumatic brain injury (TBI), also known as head injury or brain injury, refers to the head injury caused by mechanical impact. It is necessary to develop effective new therapies for TBI injury. Gastrodin (GAS) is the main bioactive ingredient from the rhizome of Gastrodia elata and has significant therapeutic effect on nervous system diseases. However, the protective effects of GAS on brain tissue and related regulatory mechanism in traumatic brain injury remain elusive. Herein, we explored the role of GAS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Growing evidence has shown that NLRP3 inflammasome‐mediated pyroptosis was involved in the pathogenesis of TBI. Yang et al revealed that Gastrodin suppressed NLRP3 inflammasome signaling pathway, and therefore inhibited pyroptosis, reduced brain tissue injury, and improved functional recovery of injury nerve in TBI rats 31 . Moreover, Yuan et al found that interference of hypoxia‐inducible factor‐1α (HIF‐1α) decreased the expressions of NLRP3, GSDMD‐N and cleaved caspase‐1 in the injured cortex after TBI, suggesting that HIF‐1α aggravated NLRP3 inflammasome‐mediated pyroptosis in TBI 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence has shown that NLRP3 inflammasome‐mediated pyroptosis was involved in the pathogenesis of TBI. Yang et al revealed that Gastrodin suppressed NLRP3 inflammasome signaling pathway, and therefore inhibited pyroptosis, reduced brain tissue injury, and improved functional recovery of injury nerve in TBI rats 31 . Moreover, Yuan et al found that interference of hypoxia‐inducible factor‐1α (HIF‐1α) decreased the expressions of NLRP3, GSDMD‐N and cleaved caspase‐1 in the injured cortex after TBI, suggesting that HIF‐1α aggravated NLRP3 inflammasome‐mediated pyroptosis in TBI 32 .…”
Section: Discussionmentioning
confidence: 99%
“…30 suppressed NLRP3 inflammasome signaling pathway, and therefore inhibited pyroptosis, reduced brain tissue injury, and improved functional recovery of injury nerve in TBI rats. 31 Moreover, Yuan et al found that interference of hypoxia-inducible factor-1α…”
Section: Exosome Protected Primary Cultured Neurons From Tbimentioning
confidence: 99%
“…The GAS content is the most appreciated analytical marker for the quality standardization of P. chinensis (Zhang et al, 2019). The mechanism of GAS action is gradually being understood and recognized Yang et al, 2022). Several reports have shown that the content of GAS in P. chinensis was higher than the content in G. elata, one of the major sources of GAS (Zhang et al, 2019;Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…TBI induces activation of the NLRP3 inflammasome in neurons, astrocytes, and microglia in the cortex, and activated caspase-1 promotes cleavage of pro-interleukin (IL)-1β, pro-IL-18, and the amino terminus of gasdermin-D (GSDMD) ( 31 ). Cleaved IL-1β, IL-18, and GSDMD ultimately cause cell pyroptosis, which is accompanied by the release of pro-inflammatory cytokines ( 32 , 33 ). Numerous studies have demonstrated that knockout or pharmacologic inhibition of the NLRP3 inflammasome can alleviate neuroinflammation and improve neurological outcomes after brain injury ( 34 36 ).…”
Section: Traumatic Brain Injury and Neuroinflammationmentioning
confidence: 99%